CFD Analysis of a solar flat plate collector with different cross sections - Andrade Cando, Anthony Xavier; Quitiaquez Sarzosa, William; Toapanta, Luis Fernando (Enfoque UTE, 2020)
Low and medium solar heating systems used for domestic and industrial applications, such as water and space heating, usually utilize solar flat plate collectors in order to absorb solar thermal energy converting it into heat and then transferring the heat to a fluid (usually water or air) that flows through it. The aim of this study is to evaluate the solar flat plate collector’s efficiency and the fluid behavior inside the pipeline with three different cross sections, whose hydraulic diameters are 10, 5.12 and 6.16 mm, by using ANSYS Fluent. The results obtained from the Computational Fluid Dynamics (CFD) tool showed that the collector with the Type I cross section reached temperatures up to 330 K at the pipe outlet obtaining an efficiency of 68 %, higher than those of Types II and III, whose efficiencies were 51 % and 60 %, respectively. Type I cross section also presented the lowest values in both speed and pressure drop, these being 0.266 m/s and 108.3 Pa, respectively.